PENGARUH BUDAYA ORGANISASI, LINGKUNGAN KERJA, DISIPLIN KERJA DAN PENGEMBANGAN KARIR TERHADAP PRESTASI KERJA PEGAWAI (Studi Kasus Kantor Dinas Sosial Pemberdayaan Perempuan dan Keluarga Berencana Kabupaten Rembang) - Sholikhah, Nur Isnaini Mirâ€™atus; Nurhidayati, Anik (JAB (Jurnal Akuntansi & Bisnis), 2020)
ABSTRACTThis study aims to prove the influence of organizational culture, work environment, work discipline and career development on employee work performance (Study at DINSOSPPKB Office in Rembang Regency). The type of data used in this study is subject data with primary data sources. Data collection was carried out using a survey method through the distribution of questionnaires directly to respondents, namely employees. The population in this study is all employees, amounting to 55 employees and used as a sample of 55 respondents. The data analysis method used is multiple linear regression analysis and data testing is performed with the assistance of SPSS version 20. The results of this study indicate that organizational culture, work environment and work discipline partially have a significant positive effect on employee performance, career development has a significant positive effect on employee performance. Organizational culture, work environment, work discipline and career development simultaneously have a significant positive effect on employee work performance (Study at the DINSOSPPKB office in Rembang Regency). Overall the ability of the independent variable in explaining the variation of the dependent variable is 72.6%, while the remaining 27.4% is influenced by other factors outside the research model.Â Keywords: Organizational Culture, Work Environment, Work Discipline, Career Development and Work Achievement